Assessment of environmental pesticides exposure of farmers living nearby the paddy fields using mathematical modelling - An Nurainee Jais (2020)
Paddy farmers can be exposed to pesticides while handling pesticides, but they may also be indirectly exposed to applied pesticides in the fields, by living nearby the agricultural fields. This study investigates how pesticide usage of the farmers in the paddy field may affect pesticide exposure and associated risk for paddy farmers living 100 m downwind from the treated area. A mathematical model developed by Wong et al (2017) was used to estimate the aggregated daily exposure to pesticide via inhaled vapour and indirect dermal exposure with contaminated ground. Risk was expressed as a hazard quotient (HQ) based on the total estimated exposure from the model and the no observed (adverse) effect level (NO(A)EL) for reproductive/developmental effects for the respective active substances. Results show that the aggregated HQs at 100 m proximity from paddy fields were <1, indicating relatively low risk of adverse development/reproductive effects among the selected paddy farmers.